2021
DOI: 10.3390/healthcare9040451
|View full text |Cite
|
Sign up to set email alerts
|

How Safety Climate Influences the Willingness to Stay of Nursing Staff during the COVID-19 Outbreak

Abstract: The outbreak of COVID-19 in China at the beginning of 2020 has made the problems that the aged care agency face with large mobility and high turnover of aged nursing staff become more serious. Aiming at this problem, this paper incorporates psychological capital and social panic into the model from the perspective of the organizational safety climate and constructs a theoretical model of the mechanism of the effect on nursing staff’s willingness to stay in the context of the outbreak. Through a questionnaire s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(35 reference statements)
0
4
0
1
Order By: Relevance
“…On the other hand, studies have reported that psychological capital has a positive impact on organizational commitment [36,50]. Employees with better psychological capital tend to keep a strong sense of belonging to their jobs, remain in close contact with colleagues, and are more willing to stay in the organization and play their roles [18,40,41]. NAs need to maintain good communication with their leaders and colleagues, and actively participate in organizational activities to promote an enjoyable team climate and a sense of belonging to their jobs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, studies have reported that psychological capital has a positive impact on organizational commitment [36,50]. Employees with better psychological capital tend to keep a strong sense of belonging to their jobs, remain in close contact with colleagues, and are more willing to stay in the organization and play their roles [18,40,41]. NAs need to maintain good communication with their leaders and colleagues, and actively participate in organizational activities to promote an enjoyable team climate and a sense of belonging to their jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have found that career adaptability has a positive impact on hope, resilience, and self-efficacy [37][38][39], all of which are major components of psychological capital. In addition, it has been found that psychological capital can contribute to reducing burnout and enhancing career identity [40], and it has a positive effect on reducing turnover intention [18,41]. In addition, Yim [42] found that psychological capital could mediate the association between occupational stress and turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies have reported that psychological capital has a positive impact on organizational commitment [37,50]. Employees with better psychological capital tend to keep a strong sense of belonging to their jobs, remain in close contact with colleagues, and are more willing to stay in the organization and play their roles [18,41,42]. NAs need to maintain good communication with their leaders and colleagues, and actively participate in organizational activities to promote an enjoyable team climate and a sense of belonging to their jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have found that career adaptability has a positive impact on hope, resilience, and self-e cacy [38][39][40], all of which are major components of psychological capital. In addition, it has been found that psychological capital can contribute to reducing burnout and enhancing career identity [41], and it has a positive effect on reducing turnover intention [18,42]. In addition, Yim [43] found that psychological capital could mediate the association between occupational stress and turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…As profissões relacionadas com os cuidados de saúde apresentam características únicas que a distinguem das outras, uma vez que a sua ação se centra não só nas pessoas que trabalham na organização, mas também nos utentes. Com o surgimento da pandemia de COVID-19, as questões associadas à perceção de risco e aos comportamentos de segurança ganharam novo ímpeto (e.g., Qianlan et al, 2020) perceção de risco, podem interferir diretamente no desempenho da organização assim como na prestação de melhores cuidados de saúde (e.g., Wang et al, 2021).…”
Section: Introductionunclassified